2012
DOI: 10.1096/fasebj.26.1_supplement.1150.8
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine opens intrapulmonary arteriovenous anastomoses in healthy humans at rest

Abstract: During exercise or while breathing hypoxic gas mixtures large diameter intrapulmonary arteriovenous anastomoses (IPAVA) open and can be detected with saline contrast echocardiography (SCE). The mechanisms regulating these vessels remain unknown, but both of these conditions activate the sympathetic nervous system and increase plasma catecholamine concentrations. We hypothesized that exogenously increasing the plasma epinephrine concentration would open IPAVA. Using SCE, we studied 5 subjects at rest, before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Therefore, as verified by various authors through the TTSCE and 99mTc-MAA techniques mentioned above (14,15,17,19,20,21,22,24,25), in this study, the presence of IPAVA was confirmed in healthy humans in conditions of both normoxia (during exercise) and hypoxia (at rest and during exercise). Unfortunately, as already pointed out, in normoxia at rest, the t measure was underestimated; therefore, it was not possible to verify, in this study, if IPAVA are open during this condition, although it should be emphasized that various authors (19,20) have verified that in healthy humans, in normoxia at rest, IPAVA are closed, but only in the vast majority of cases and not in all subjects (26).…”
Section: Ipava Blood Flow ( Ipava )supporting
confidence: 81%
See 4 more Smart Citations
“…Therefore, as verified by various authors through the TTSCE and 99mTc-MAA techniques mentioned above (14,15,17,19,20,21,22,24,25), in this study, the presence of IPAVA was confirmed in healthy humans in conditions of both normoxia (during exercise) and hypoxia (at rest and during exercise). Unfortunately, as already pointed out, in normoxia at rest, the t measure was underestimated; therefore, it was not possible to verify, in this study, if IPAVA are open during this condition, although it should be emphasized that various authors (19,20) have verified that in healthy humans, in normoxia at rest, IPAVA are closed, but only in the vast majority of cases and not in all subjects (26).…”
Section: Ipava Blood Flow ( Ipava )supporting
confidence: 81%
“…However, both techniques made it possible to detect blood flow through IPAVA in healthy humans in normoxia during exercise (14,20) and, at rest and during exercise, in hypoxia (19,15). Furthermore, the simultaneous use of the two techniques, TTSCE and 99mTc-MAA, led to consistent data (24).…”
Section: Ipava Blood Flow ( Ipava )mentioning
confidence: 97%
See 3 more Smart Citations